2008
DOI: 10.1007/s00277-008-0667-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of Helicobacter pylori eradication in patients with idiopathic thrombocytopenic purpura: 7-year follow-up prospective study

Abstract: Helicobacter pylori eradication is useful for improvement of a half of patients with idiopathic thrombocytopenic purpura (ITP), but its long-term therapeutic efficacy has not been elucidated. We investigated the long-term efficacy of H. pylori eradication in 30 cases with ITP that were included in our previous study regarding the association between H. pylori infection and ITP. Twenty-one cases were positive and nine cases were negative for H. pylori infection. H. pylori eradication therapy including secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…ITP in adults generally appears in a chronic form, with the definition of chronic ranging from ITP of at least 6 months duration to at least 12 months duration [7,[9][10][11][12]. Causal factors may include active Helicobacter pylori infection; H. pylori eradication therapy appears to improve thrombocytopenia in some ITP patients [13][14][15][16][17][18]. ITP appears to be more frequent in women, particularly between the ages of 30-60 years [10,11,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…ITP in adults generally appears in a chronic form, with the definition of chronic ranging from ITP of at least 6 months duration to at least 12 months duration [7,[9][10][11][12]. Causal factors may include active Helicobacter pylori infection; H. pylori eradication therapy appears to improve thrombocytopenia in some ITP patients [13][14][15][16][17][18]. ITP appears to be more frequent in women, particularly between the ages of 30-60 years [10,11,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Successful eradication against Helicobacter pylori (H. pylori) had been increasingly demonstrated to recover platelet counts in patients with idiopathic thrombocytopenic purpura (ITP) [1], and reports on the long term outcome of this established treatment have been published [2][3][4]. In contrast, we had reported a reduction in platelet counts 8 weeks after the successful eradication therapy for the pathogen in non-ITP patients [5].…”
Section: Introductionmentioning
confidence: 69%
“…A meta-analysis and a systematic review showed a strict correlation between H. pylori eradication and an increased platelet count [3,14]. As the long-term efficacy of H. pylori eradication treatment has been confirmed in several recent reports [22][23][24][25][26], it seems that H. pylori eradication may prove a safe and radical Many factors have been investigated to clarify the pathogenesis of H. pylori-induced thrombocytopenia. An immunological mimicry between platelet and H. pylori antigens has been discussed in several studies.…”
Section: Discussionmentioning
confidence: 95%
“…Of note, previous studies indicated that the incidence of atrophic gastritis was lower in both American whites and Canadians than in Japanese [42,43]. With regard to ITP, the platelet response rate after eradication for H. pylori-positive ITP patients was high in Japanese studies (overall rate was 58%), as well as in 2 Italian studies (56 and 74%, respectively), while the results of a Spanish, a Serbian, a Mexican, a Turkish, and 2 American studies demonstrated relatively low response rates (13,26,14,44,29, and 7%, respectively) [14]. More recently, favorable response rates were reported from Colombia and Iran (81 and 48%, respectively) [44,45].…”
Section: Discussionmentioning
confidence: 95%